2012
DOI: 10.4049/jimmunol.1102998
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Neuronal Recognition by CD8 T Cells Elicits Central Diabetes Insipidus

Abstract: An increasing number of neurologic diseases is associated with autoimmunity. The immune effectors contributing to the pathogenesis of such diseases are often unclear. To explore whether self-reactive CD8 T cells could attack CNS neurons in vivo, we generated a mouse model in which the influenza virus hemagglutinin (HA) is expressed specifically in CNS neurons. Transfer of cytotoxic anti-HA CD8 T cells induced an acute but reversible encephalomyelitis in HA-expressing recipient mice. Unexpectedly, diabetes insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…Somatic upregulation of MHC I on neurons may also mark these cells for elimination by anti‐neuronal T cells, leading to loss of neurons in otherwise normal appearing gray matter. Indeed several studies have shown that targeting neoantigens to CNS neuronal subsets results in rapid clearance by antigen‐specific CD8 + T cells 15, 69, 70, 71. Finally, anterograde transport of MHC class I molecules into the distal axon makes these molecules available near the site of inflammation, where they may increase vulnerability to attack by autoreactive anti‐axonal CD8 + T cells 10.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic upregulation of MHC I on neurons may also mark these cells for elimination by anti‐neuronal T cells, leading to loss of neurons in otherwise normal appearing gray matter. Indeed several studies have shown that targeting neoantigens to CNS neuronal subsets results in rapid clearance by antigen‐specific CD8 + T cells 15, 69, 70, 71. Finally, anterograde transport of MHC class I molecules into the distal axon makes these molecules available near the site of inflammation, where they may increase vulnerability to attack by autoreactive anti‐axonal CD8 + T cells 10.…”
Section: Discussionmentioning
confidence: 99%
“…T-Cell Differentiation and T-Cell Transfer. HA-specific CD8 + CTL and HA-specific CD4+ Th1 were generated from F1 CL4-TCR mice and F1 6.5-TCR mice, respectively, as described (46,47 Histopathology. Tissues were fixed in 4% (wt/vol) paraformaldehyde, conserved in 70% (vol/vol) ethanol, and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…27 Interestingly, significant weight loss was observed in CamK-HA mice implanted with 4T1-HA tumor following transfer of na€ ıve HA-specific CD4C T cells and CD8C T cells. Seventy two percent of the CamK-HA animals showed over 5% loss of their initial weight (Fig 2A).…”
Section: Resultsmentioning
confidence: 99%